Chemical and process plant commissioning handbook : a practical guide to plant system and equipment installation and commissioning - Killcross, Martin (Amsterdam ; Boston : Elsevier/Butterworth-Heinemann, 2012)
"A guide and reference to preparing a systematic methodology for converting a newly constructed plant, as well as streamlining equipment into an operational process unit. [...] The reference focuses on the critical safety assessment and inspection regimes necessary to ensure that new plants are compliant with OSH (A) and environmental requirements"--P. [4] of cover.
Includes index.
Keywords: Building commissioning -- Handbooks, manuals, etc; Chemical plants -- Design and construction -- Standards